The International Factor in the Domestic Political Transformation in the Kosovo's* “Albanian World” - E. G. Entina (Международная аналитика, 2021)
The Kosovo issue is predominantly researched in academic and expert literature from an international political perspective. However, in light of common socio-political processes taking place in Europe during the last ﬁ ve-seven years, the study of its internal political component, namely the political party transformation under the inﬂ uence of external factors and the international community, regional stabilization eﬀ orts is no less important. Based on J. Sartori’s classiﬁ cation of party systems and R. Harmel and K. Janda’s theory of party change, the article studies the role of international actors, in particular the European Union, played in the institutional transformation of the political party transformation in the Albanian Kosovo. It also studies what opportunities and barriers appeared as a result of the EU’s involvement. The paper explains why the complex conﬁ guration of the international mission in Kosovo in practice did not increase its legitimacy and establish an institutional system of governance but instead resulted in a loss of the mission’s credibility. The paper analyses and describes the process of political party transformation in Kosovo’s “Albanian world” and highlights the signiﬁ cant milestones in the development of a party system involving those that had been borne out of the Kosovo conﬂ ict. The article explains their possible ways of transformation in the future. It also explains the success factors of the populist “Self-Determination” movement and how sustainable this success has been in the changing international balance.